Medicine and humanism in the time of COVID-19. Ethical choices - Doldi, Marco; Moscatelli, Andrea; Ravelli, Angelo; Spiazzi, Raffaele; Petralia, Paolo (Acta Biomedica Atenei Parmensis, 2020)
The Covid-19 pandemic has been the most defining event of our era. The world of healthcare has experienced first-hand the dramatic situation of treating patients in the face of the dangers of contagion and limited resources. Difficult choices have everywhere been made alongside ethical reflection. Now that, at least in our part of the world, viral infection seems to be broadly on the decline, there is an urgent need for fresh, anthropological, ethical reflection. It is important to avoid being unprepared in the event of further occasions, but above all, to now think in global terms. This is because the pandemic has forced us to recognise the urgency of building alliance in healthcare and a balanced relationship with the environment.